Decline of post-neoliberal regionalism in South America: Weaknesses of “pink tide” political leadership on Defense policies - Emilse Eliana Calderón (Íconos)
This article discusses the evolution of post-neoliberal regionalism in South America as implemented by the Union of South American Nations (UNASUR). A qualitative and multi-causal approach to political and social phenomena will be used, together with a theoretical-conceptual viewpoint close to neoclassical realism. Special consideration is given to the South American Defense Council (CDS): An unprecedented attempt to build consensus between participant countries on Defense issues and to develop effective confidence-building measures among them. The weakening of the Council as a consequence of the changing political and ideological trends -prevalent in the second decade of the current century-, is granted particular consideration. The article explains the reasons why it was so easy for participant Governments to abandon post-neoliberal regionalism, as soon as the so-called “pink tide” receded. Finally, evidence is provided that shows that domestic variables played a crucial role in accounting for the demise of this new regional security model. Structural internal weaknesses within the regional States also played a major part in limiting the capacity of political leaders to sustain their control over Defense policies. Factors related to the international system are seen as of secondary importance. Although the United States is not a central player in these developments, it certainly had some influence in reinforcing and encouraging the reversal of the policies initiated and endorsed by UNASUR and the CDS.